2006
DOI: 10.1149/1.2358843
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Alloy Corrosion Inhibition by Vanadates

Abstract: The inhibition of Al alloy corrosion by vanadates was studied in this work. Vanadium speciation is very complicated and vital to the inhibition efficacy. Critical conditions for decavanadate polymerization from clear metavanadate solutions were investigated. Decavanadate only formed when metavanadate was added to solutions of pH 3 or less. It was not possible to change the pH of a metavanadate solution without forming decavanadates, creating an orange-colored solution. According to 51 V nuclear magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(116 citation statements)
references
References 55 publications
4
109
1
2
Order By: Relevance
“…Previous findings showed that orange decavanadate solutions did not have a significant effect on the kinetics of the ORR [39]. The effects of injecting orange decavanadate solutions to the AA2024/Cu split cell are shown in Fig.…”
Section: Split Cell Techniquementioning
confidence: 84%
See 3 more Smart Citations
“…Previous findings showed that orange decavanadate solutions did not have a significant effect on the kinetics of the ORR [39]. The effects of injecting orange decavanadate solutions to the AA2024/Cu split cell are shown in Fig.…”
Section: Split Cell Techniquementioning
confidence: 84%
“…Previous results indicated that the rate of the ORR in orange solutions containing decavanadates was only slightly lower than in the base solution with no vanadate [39]. Thus, when testing decavanadates by the split cell, a smaller reduction in galvanic current was to be expected.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…10 Work has revealed that crevice corrosion of aluminium can be inhibited in a sodium chloride solution. 11 Metavanadates have been shown to inhibit oxygen reduction on AA 2024-T3 alloy, 12,13 although no effect was found with decavanadate. 13 It has been reported that inhibition does not involve reduction of vanadate.…”
Section: Introductionmentioning
confidence: 99%